The modern law of contract - Stone, Richard 1951-; Devenney, James (Routledge Taylor & Francis Group, c2017., 2017)
The "Modern Law of Contract" is a clear and logical textbook, written by an experienced author team with well over 50 years' teaching and examining experience.